Pemanfaatan Bahan Alam dalam Pembuatan Ecoprint pada Siswa Kelas V Dan VI SDN Pegambiran 2 - Siti Zahra Fatimah; Siti Rahma; Siti Nursya'adah; Theresia Ok’twoka Ekgiyoga; Arief Hidayat Afendi; Fahrur Rizal; Slamet Hidayat (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
Ecoprint is a technique for printing natural patterns on fabric by utilizing natural materials such as leaves and flowers. This community service activity aims to introduce the ecoprint technique to V and VI students at SDN Pegambiran 2 Kota Cirebon while enhancing their creativity and environmental awareness. The method used in this activity is hands-on practice (learning by doing) with the pounding technique, which involves striking leaves and flowers so that their pigments transfer onto the fabric. The results of the activity indicate that students were highly enthusiastic about each stage of the ecoprint-making process, from selecting materials and arranging patterns to the printing and color fixation process. Additionally, students gained new insights into the utilization of natural resources around them as eco-friendly natural dyes. The students' artworks demonstrated good pattern and color quality, with clear color variations and patterns that matched the shapes of the leaves used. This activity not only improved students' artistic skills but also introduced them to an environmentally friendly printing technique and fostered values of nature conservation. Keywords : Ecoprint, Student creativity, Environmental awareness, Natural dye